An evaluation of the experiences of the hidden curriculum of Black and minority ethnic undergraduate health and social care students at a London university. Issue 3 (16th March 2022) - Webb, Justin; Arthur, Ryan; McFarlane-Edmond, Pansy; Burns, Thomas; Warren, Digby
ABSTRACT: Black and minority ethnic (BME) students are less likely to achieve a first or upper-class second degree than White students. This evaluation investigated the experiences of BME Health and Social Care students at a London university of the hidden curriculum, thematically analysed through a critical race lens. Four overarching themes were identified, (1) super-visible ethnicity, (2) the negative depiction of BME lived experiences, (3) self-depreciation and self-confidence and (4) separation. Recommendations at an institution-level are made in the areas of staff diversity, language support, student registration experiences and canteen costs. Recommendations at a course-level are made in the areas of co-creation of the curriculum, student belonging, academic and literacy skill development. The recommendations are underpinned by a critical pedagogy, including culturally sensitive teaching strategies and the development of meaningful staff-student partnerships. The recommendations made may be applicable to other Higher Education Institutions with a diverse student cohort where the attainment gap is prevalent.